Classroom Management Techniques Implemented by EED Lecturers UMY - Andin Indah Kumalasari (PBI 15 UMY 023, 2015)
*23 Back to the researcher’s experience in her past elementary and high school, lecturers used to give physical punishment to the students who conduct misbehavior. According to Talwar, Carlson, and Lee as cited in Kinsley, Abigail, Gameli, Rita, and Nkansah, (2013), physical punishment has been found to negatively impact the academic performance of children. Indeed, punishment is one way conducted by particular lecturers to manage the classroom. In English Education Department (EED) Universitas Muhammadiyah Yogyakarta (PBI), through the researcher’s experiences as a student over there, lecturers were assumed applying different classroom managements. This research was aimed at finding the techniques the lecturers used to manage the class. Also, the possible challenge faced and solutions were also the focus of this study. This research was designed as a case study which took place at EED UMY. To gather the data, the researcher conducted interview to four lecturers who were in charge in second semester. This research found that there were many techniques implemented by the lecturers, such as, imposing discipline, establishing positive classroom climate, and effective communication channel. Also, each technique brought different challenges and various solutions.